2006
DOI: 10.1016/j.clinbiomech.2006.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among body weight, joint moments generated during functional activities, and hip bone mass in older adults

Abstract: Objective-To investigate the relationships among hip joint moments produced during functional activities and hip bone mass in sedentary older adults.Methods-Eight male and eight female older adults (70-85 yr) performed functional activities including walking, chair sit-stand-sit, and stair stepping at a self-selected pace while instrumented for biomechanical analysis. Bone mass at proximal femur, femoral neck, and greater trochanter were measured by dual-energy X-ray absorptiometry. Three-dimensional hip momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…One research group found that in individuals without MS aged 30 to 49, hip joint moments can explain up to 58 percent of variance in BMC, more so than variance in BMD, independent of body size [59]. An even stronger correlation was found in another study of older adults without MS, for whom dynamic hip load independently predicted up to 93 percent of variance in BMC and 73 percent of variance in BMD [60]. However, other researchers have reported that current physical activity does not affect BMD in postmenopausal women without MS [63] and BMD of the PF is not associated with dynamic hip load in young women without MS [64].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…One research group found that in individuals without MS aged 30 to 49, hip joint moments can explain up to 58 percent of variance in BMC, more so than variance in BMD, independent of body size [59]. An even stronger correlation was found in another study of older adults without MS, for whom dynamic hip load independently predicted up to 93 percent of variance in BMC and 73 percent of variance in BMD [60]. However, other researchers have reported that current physical activity does not affect BMD in postmenopausal women without MS [63] and BMD of the PF is not associated with dynamic hip load in young women without MS [64].…”
Section: Discussionmentioning
confidence: 75%
“…That physical activity and exercise positively affect BMD in healthy women across the lifespan is well established [55][56][57]. Several studies in non-MS populations have shown that PF BMD and BMC, in particular, are strongly associated with dynamic load on the hip [43,[58][59][60] and with accelerometer counts [41,[61][62]. One research group found that in individuals without MS aged 30 to 49, hip joint moments can explain up to 58 percent of variance in BMC, more so than variance in BMD, independent of body size [59].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced quadriceps fatigability observed in the present study may be a result of the obese women having adapted to greater body mass because the excess body mass constantly carried by these obese individuals (weight-bearing effects) during daily activities and leisure creates a prolonged level of muscular exertion that mimics an exercise load, inducing favorable fatigue-resistant effects. 8,30 Conversely, the reduced amount of fast powerful movements secondary to excess body mass may contribute to a loss of fast-twitch motor units (type IIb), resulting in a loss of strength. 12,27,28,31,32 We also found a correlation between fatigue and carbohydrate intake, which may be linked to the fact that high intensity exercises mainly use anaerobic metabolism (glycolysis), recruiting type II muscle fibers (glycolytic fibers).…”
Section: Discussionmentioning
confidence: 98%
“…For walking, the peak adduction moment is of particular interest as it is a large component of the inter-segmental moments at the hip that must be balanced by internal muscle forces throughout stance. It occurs in the same time region as the peak-resultant joint force and bending moment, as measured in vivo (Bergmann et al, 1995), and has been used previously as a surrogate measure of the joint loading (Schipplein and Andriacchi, 1991;Hurwitz et al, 1998;Moisio et al, 2004;Andriacchi and Mundermann, 2006;Wang et al, 2006;Thorp et al, 2006). The simplified marker set used in this study was selected on the basis of the specific questions addressed which focused on the three-dimensional external joint moments at the hip and sagittal and frontal plane hip motions.…”
Section: Discussionmentioning
confidence: 99%